Including Fibroblast Growth Factor-21 in Combined Biomarker Panels Improves Predictions of Liver Steatosis Severity in Children - Man-Chin Hua; Man-Chin Hua; Jing-Long Huang; Jing-Long Huang; Ching-Chih Hu; Ching-Chih Hu; Tsung-Chieh Yao; Tsung-Chieh Yao; Ming-Wei Lai; Ming-Wei Lai; Ming-Wei Lai (Frontiers Media S.A., 2019)
Background: Previous studies reported conflicting results regarding the association between fibroblast growth factor-21 (FGF-21) and non-alcoholic fatty liver disease (NAFLD). This study aimed to evaluate the feasibility of combining FGF-21, obesity indices, and biochemical tests for predicting high-grade liver steatosis in children.Methods: A total of 203 children and adolescents aged 5-18 years were enrolled, and their anthropometric data, body composition, liver ultrasound score for NAFLD (range, 0-6), biochemical test results, and FGF-21, leptin, and adiponectin levels were analyzed. Children were categorized according to body mass index (BMI) and NAFLD scores. Univariate analysis and multivariate linear regression were used to identify independent predictors for the degree of liver steatosis. The accuracy of the models was also evaluated using a receiver-operating characteristic (ROC) curve.Results: FGF-21 levels were significantly higher in subjects with high-grade liver steatosis (P < 0.001). In obese and overweight children, regression analysis indicated that higher BMI and higher gamma-glutamyl transferase (γ-GT), triglycerides (TG), and FGF-21 levels were independent risk factors strongly correlated with NAFLD scores. FGF-21 combined with any of the above parameters showed a larger area under the ROC (AUROC, 0.861-0.873) than either parameter used alone. Overall, the best performance was obtained by combing FGF-21, γ-GT, and TG, with an AUROC of 0.871, specificity of 82.54%, and sensitivity of 83.78% for predicting high-grade liver steatosis.Conclusion: BMI, FGF-21, γ-GT, and TG levels were strongly correlated with liver steatosis severity. Including FGF-21 in the biomarker panels may improve the accuracy for identifying obese and overweight children with high-grade liver steatosis.